Uji disolusi terbanding tablet parasetamol - Adam, Denis Tesalonika Ernest; I Gusti Ngurah Agung Dewantara Putra (Program Studi Akuntansi IKOPIN, 2022)
The dissolution test was conducted to determine the effect of the formulation andfabrication processes on the dissolution profile in estimating the bioavailability andbioequivalence between the test and comparison products. The comparable dissolutiontest used 3 different dissolution mediums were hydrochloric acid pH 1,2 or simulatedgastric fluid without enzymes, citrate buffer medium pH 4.5 and phosphate buffer medium pH 6.8 or simulated intestinal fluid without enzymes. The first study used 12 tablets of Panadol which were randomly selected. Then, the results were comparedusing two independent model methods were the difference factor (f1) and the similarity factor (f2). Based on this, the similarity factor in the three media is in the acceptablerange of 50-100. Another study conducted testing using acetaminophen samples purchased fromRochem, Turkey. The results obtained were in accordance with USP guidelines namelyconventional acetaminophen tablets should be released at at least 80% of the labeledamount in 30 minutes. In another study also compared the dissolution profile of 4 coatedand noncoated tablets. All formulations within the first 45 minutes had a drug release of more than 85%.